Solid electrolyte, preparation method thereof and self-generating secondary battery containing the same

By developing solid electrolytes that contain a compound that combined with chlorpheniopromal or chimodoline and hydrogen fluoride, and add lithium salt to the crystalline structure, the safety and ion conduction rate of liquid electrolytes in the existing secondary battery have been solved. The solid electrolyte.

CN112106214BActive Publication Date: 2025-01-28IND UNIV COOP FOUND HANYANG UNIV ERICA CAMPUS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN201980026046.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-04-16
Filing Date
2019-04-16
Publication Date
2025-01-28
Estimated Expiration
2039-04-16

AI Technical Summary

Technical Problem

The liquid electrolytes of existing secondary batteries have risks of volatility, leakage and explosion, and the ion conductivity of solid electrolytes is low, making it difficult to meet the needs of lightweight and miniaturization.

Method used

The development of a solid electrolyte containing a compound that combines cations and anionic ions is used as a cationic ionic ion and hydrogen fluoride as an anion, and the lithium salt is added to the crystalline structure to improve the ion conduction rate.

Benefits of technology

The solid electrolyte of high ion conduction is reduced, reducing the weight and volume of the secondary battery, while improving safety, and avoiding the volatilization and explosion risk of liquid electrolytes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112106214B_ABST
    Figure CN112106214B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte. The solid electrolyte may include a compound in which a cation and an anion are combined, wherein the cation includes thiophenium, and the anion includes fluorine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte and a method for preparing the same, and more particularly to a solid electrolyte comprising a compound in which cations and anions are combined, a method for preparing the same, and a self-generating secondary battery comprising the same. Background Art

[0002] Generally, a secondary battery is formed by a positive electrode, a negative electrode and an electrolyte, and the electrolyte is formed between the positive electrode and the negative electrode. The secondary battery is used in portable electronic devices such as smart phones. In the case of the portable electronic device market, there is a trend to manufacture electronic devices with thin thickness and flexible characteristics. Therefore, it is necessary to make the secondary battery lightweight and miniaturized. However, the electrolyte of the current secondary battery mainly uses a liquid substance mixed with an organic solvent and a salt containing lithium or sodium ions. In this case, as the secondary battery is used, the organic solvent of the electrolyte may evaporate or leak, and expand as the temperature rises, thereby posing a risk of explosion. Therefore, in essence, a solid electrolyte with improved stability is required compared to a liquid electrolyte. In this case, compared with a liquid electrolyte, a general solid electrolyte has a low ion conductivity. In order to solve the above problems, research on a solid electrolyte containing an ionic substance is underway.

[0003] For example, Korean Patent Publication No. 10-2014-0046611 (Application No. 10-2012-0111557) provides the following ionic liquid polymer electrolyte composition, that is, an ionic liquid monomer having a vinyl group and an ionic group, an organic electrolyte, and a cross-linking agent having at least two double bonds at the end, wherein the ionic group comprises a cation and an anion. Based on this, a preparation method of an ionic liquid polymer electrolyte composition for a lithium secondary battery that can solve the problem of electrolyte leakage and has excellent flame retardant properties is disclosed. Summary of the invention

[0004] Technical issues

[0005] A technical problem to be solved by the present invention is to provide a solid electrolyte and a preparation method thereof.

[0006] Another technical problem to be solved by the present invention is to provide a solid electrolyte comprising a compound having a crystalline phase in which cations and anions are combined, and a preparation method thereof.

[0007] Another technical problem addressed by the present invention is to provide a solid electrolyte having high ion conductivity and a method for preparing the same.

[0008] Another technical problem to be solved by the present invention is to provide an organic piezoelectric material and a preparation method thereof.

[0009] Another technical problem to be solved by the present invention is to provide an organic piezoelectric material comprising a compound in which cations and anions are combined and have a crystalline phase, and a preparation method thereof.

[0010] Another technical problem to be solved by the present invention is to provide an organic piezoelectric material with high piezoelectric performance and a preparation method thereof.

[0011] The technical problems to be solved by the present invention are not limited to the above problems.

[0012] Technical Solution

[0013] In order to solve the above problems, the present invention provides a solid electrolyte.

[0014] According to one embodiment, the solid electrolyte may include a compound in which a cation and an anion are combined, the cation includes thiophenium, and the anion includes hydrogen fluoride.

[0015] According to an embodiment, the compound may include an alkyl group bonded to the sulfur element of the thiophenium, and the alkyl group includes one of a methyl group, an ethyl group, a propyl group, or a butyl group.

[0016] According to one embodiment, the longer the chain of the alkyl group is, the lower the ion conductivity of the compound can be.

[0017] According to one embodiment, the compound may include a methyl group bonded to the sulfur element of the thiophenium, and in a heat flow spectrum based on differential scanning calorimetry, has a first crystalline phase in a temperature range of 28°C to 90°C and has a second crystalline phase in a temperature range of 22°C to 28°C.

[0018] According to one embodiment, the solid electrolyte may further include a lithium salt, and the unit cell of the compound has an orthorhombic crystal structure, wherein the cations are provided to the vertices and the centers of the faces of the crystal structure, the anions are provided to the middle of the edges of the crystal structure, and the lithium salt is provided to any interstitial sites of the crystal structure.

[0019] According to one embodiment, the ion conductivity of the solid electrolyte may be increased as the concentration of the lithium salt increases.

[0020] According to one embodiment, the present invention provides a methyl group that can be bonded to the sulfur element of the thiophenium, and has a crystalline phase in a temperature range of 28° C. to 70° C. in a heat flow spectrum based on temperature of differential scanning calorimetry.

[0021] When an external force is applied, the cations and the anions may be displaced, so that the compound has piezoelectric properties.

[0022] In order to solve the above technical problems, the present invention provides a self-generating secondary battery.

[0023] According to one embodiment, the self-powered secondary battery may include a positive electrode, a negative electrode, and an electrolyte. The electrolyte is located between the positive electrode and the negative electrode. The electrolyte includes the compound of the above embodiment and a lithium salt.

[0024] In order to solve the above technical problems, the present invention provides a solid electrolyte.

[0025] According to one embodiment, the solid electrolyte may include a compound in which a cation and an anion are combined, the cation includes thiazolium, and the anion includes hydrogen fluoride.

[0026] According to one embodiment, the compound may include an alkyl group bonded to the nitrogen element of the thiazolium, and the alkyl group includes one of a methyl group, an ethyl group, a propyl group, or a butyl group.

[0027] According to one embodiment, the compound may include an ethyl group bonded to the nitrogen element of the thiazolium.

[0028] According to one embodiment, the solid electrolyte may further include a lithium salt.

[0029] In order to solve the above technical problems, the present invention provides a solid electrolyte.

[0030] According to one embodiment, the solid electrolyte may include a compound in which cations and anions are combined, and the cations and anions are selected so as to have a maximum ion conductivity within a range that satisfies a condition that the compound has a crystalline phase.

[0031] According to one embodiment, the conditions for the above-mentioned compound to have a crystalline phase are as follows, that is, the molecular weight of the above-mentioned cation can be greater than 95g / mol, the molecular weight of the above-mentioned anion is greater than 60g / mol, and the hydrogen ion concentration (pH) of the above-mentioned anion is less than 3, so that the crystalline phase of the above-mentioned compound has flexibility and the fusion entropy of the above-mentioned compound reaches 15~25J / Kmol.

[0032] According to one embodiment, the cation may include a five-membered heterocyclic compound, wherein the heterocyclic compound includes an element selected from sulfur, nitrogen, oxygen, or phosphorus.

[0033] According to an embodiment, when the cation includes thiophenium, the anion may include one of hydrogen fluoride, cyano(nitroso)methanide or tetrazoline.

[0034] In order to solve the above technical problems, the present invention provides a method for preparing a solid electrolyte.

[0035] According to one embodiment, the method for preparing the above-mentioned solid electrolyte may include: preparing a mixed solution containing one of a thiophenium salt or a thiazolium salt and a hydrogen fluoride precursor; and reacting the above-mentioned mixed solution at a temperature below room temperature to prepare a compound of thiophenium and hydrogen fluoride or a compound of thiazolium and hydrogen fluoride.

[0036] According to one embodiment, the step of preparing the above-mentioned mixed solution may include the step of preparing the above-mentioned thiophene salt or the above-mentioned thiazolium salt, and the step of preparing the above-mentioned thiophene salt or the above-mentioned thiazolium salt includes: the step of preparing an alkyl precursor solution; the step of titrating thiophene or thiazoline into the above-mentioned alkyl precursor solution to prepare a cation source solution; and the step of reacting the above-mentioned cation source solution to prepare the thiophene salt or thiazolium salt containing the above-mentioned alkyl group, and the above-mentioned alkyl group may contain one of methyl, ethyl, propyl or butyl.

[0037] According to one embodiment, the step of preparing the mixed solution may include the step of preparing the hydrogen fluoride precursor, and the step of preparing the hydrogen fluoride precursor includes the step of preparing the hydrogen fluoride precursor by stirring a solution including hydrofluoric acid and water.

[0038] According to one embodiment, the method for preparing the above-mentioned solid electrolyte may also include: a step of preparing lithium hydride fluoride; and a step of mixing the compound of the above-mentioned embodiment and the above-mentioned lithium hydride fluoride, and performing heat treatment to prepare a lithium-coated solid electrolyte, the step of preparing the above-mentioned lithium hydride fluoride including: a step of adding a lithium salt to a hydrofluoric acid aqueous solution to prepare a source solution; and a step of reacting the above-mentioned source solution at a temperature below room temperature to prepare the above-mentioned lithium hydride fluoride.

[0039] Effects of the Invention

[0040] The solid electrolyte according to the embodiment of the present invention may include a compound in which a cation and an anion are combined, wherein the cation includes thiophenium, and the anion includes hydrogen fluoride.

[0041] Furthermore, the solid electrolyte may include the compound and a lithium salt. In this case, the unit cell of the compound may have an orthorhombic crystal structure, the thiophenium is provided to the vertices and the center of the face of the crystal structure, and the fluoride is provided to the edge center of the crystal structure. Thus, the solid electrolyte may provide the lithium salt to any interstitial position of the crystal structure.

[0042] As described above, the lithium salt can easily move within the crystal structure, and thus, in the solid electrolyte, as the concentration of the lithium salt increases, the ion conductivity can be improved.

[0043] Furthermore, as described above, the solid electrolyte may form a lithium-rich phase. In this case, the lithium-rich phase may have a relatively low melting point. In other words, the solid electrolyte may have a lower melting point than the compound, thereby reducing the melting entropy of the solid electrolyte.

[0044] Therefore, the solid electrolyte may include the compound in which the cation and the anion are combined, has a crystalline phase, and has high ion conductivity. Thus, the solid electrolyte can be easily provided as an electrolyte for a secondary battery.

[0045] The compound in which the cation containing the thiophenium and the anion containing the hydrogen fluoride are combined may be an organic piezoelectric material. In this case, the organic piezoelectric material may have a crystalline structure. When an external force is applied to the organic piezoelectric material, the cation and the anion in the single cell of the crystalline structure may be displaced, thereby the organic piezoelectric material may have piezoelectric properties.

[0046] The above-mentioned organic piezoelectric material may have a melting entropy of 15 to 35 J / Kmol. Therefore, the crystalline structure of the above-mentioned organic piezoelectric material may have flexibility (softness). In addition, the above-mentioned organic piezoelectric material may be a polycrystal composed of a plurality of tiny crystals. Therefore, the above-mentioned organic piezoelectric material may have piezoelectric properties through spontaneous ion polarization phenomenon. In this case, the above-mentioned organic piezoelectric material may have a high piezoelectric coefficient of 109pC / N at room temperature. In addition, the above-mentioned organic piezoelectric material can be prepared at room temperature or a temperature below room temperature.

[0047] Therefore, compared with the existing inorganic piezoelectric materials, the above-mentioned organic piezoelectric materials can have a low process temperature and can be prepared by polarization treatment at a relatively low voltage. Therefore, the time and cost required for the preparation process of the above-mentioned organic piezoelectric materials can be saved. Moreover, compared with the existing piezoelectric materials, the above-mentioned organic piezoelectric materials can have a high piezoelectric coefficient, and the above-mentioned organic piezoelectric materials can be easily used in various electronic devices such as self-generating secondary batteries, piezoelectric sensors, and piezoelectric actuators.

[0048] Furthermore, according to an embodiment of the present invention, the solid electrolyte may include a compound in which a cation and an anion are combined, the cation includes thiazolium, and the anion includes hydrogen fluoride. Furthermore, the solid electrolyte may include the compound and a lithium salt. The solid electrolyte may have a crystalline phase and may have high ion conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 is a flow chart for illustrating a method for preparing a solid electrolyte according to a first embodiment of the present invention;

[0050] Figure 2 A diagram showing the crystal structure of a solid electrolyte according to a first embodiment of the present invention;

[0051] Figure 3 A schematic diagram of a self-generating secondary battery including an organic piezoelectric material according to an embodiment of the present invention;

[0052] Figure 4 A diagram showing a cross-sectional view of a piezoelectric sensor including an organic piezoelectric material according to an embodiment of the present invention and a driving principle;

[0053] Figure 5 is a block diagram of a device including an organic piezoelectric substance according to an embodiment of the present invention;

[0054] Figure 6 is a flow chart for illustrating a method for preparing a solid electrolyte according to a second embodiment of the present invention;

[0055] Figure 7 It is a differential scanning calorimetry (DSC) chart of the compound of Experimental Example 1-1 of the present invention and the solid electrolyte of Experimental Example 2-3;

[0056] Figure 8 A graph showing the X-ray diffraction pattern (XRD) of the compound of Experimental Example 1-1 and the solid electrolyte of Experimental Example 2-2 of the present invention;

[0057] Fig. 9 A graph showing the ion conductivity of the compounds of Experimental Examples 1-1 to 1-4 of the present invention and the compounds of Comparative Examples 1-1 to 1-4 depending on temperature;

[0058] Fig.10 A graph showing the ion conductivity of the compound of Inventive Experimental Example 1-1 and the solid electrolytes of Experimental Examples 2-1 to 2-3 depending on temperature;

[0059] Fig.11 To take a picture of an electrolyte membrane coated with a solid electrolyte according to an embodiment of the present invention;

[0060] Figure 12 to Figure 13A graph showing cycle test results of a secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention;

[0061] Fig.14 A graph showing the capacity retention rate of the secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention at the charging and discharging speeds;

[0062] Fig.15 A graph showing resistance of a secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention in a cycle test;

[0063] Fig.16 A graph showing the piezoelectric coefficient of the organic piezoelectric material according to an embodiment of the present invention as a function of temperature;

[0064] Fig.17 A graph showing the piezoelectric coefficient of the organic piezoelectric material according to an embodiment of the present invention as a function of frequency;

[0065] Fig.18 A scanning electron microscope (SEM) image showing an organic piezoelectric material according to an embodiment of the present invention;

[0066] Fig.19 A piezoelectric microscope (PFM) image showing an organic piezoelectric material according to an embodiment of the present invention;

[0067] Fig. 20 This is a graph showing the ionic conductivity of the compounds of Experimental Examples 3-1 and 3-4 of the present invention;

[0068] Fig.21 is a differential scanning calorimetry (DSC) chart of the compound of Experimental Example 3-1 of the present invention;

[0069] Fig. 22 This is a graph showing the electrochemical window of the compound of Experimental Example 3-1 of the present invention. DETAILED DESCRIPTION

[0070] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. However, the technical concept of the present invention is not limited to the above-mentioned embodiments, but can be embodied in other forms. On the contrary, the embodiments disclosed herein are provided to make the disclosed contents complete and to fully convey the concept of the present invention to ordinary technicians in the technical field to which the present invention belongs.

[0071] In this specification, when it is mentioned that a structural element is located on other structural elements, it means that it can be directly formed on other structural elements, or a third structural element can be formed in between. In addition, in the drawings, the thickness of the film and the region is exaggerated for the purpose of effectively explaining the technical content.

[0072] Furthermore, in the multiple embodiments of this specification, the terms first, second, third, etc. are used to describe multiple structural elements, and these structural elements are not limited to these terms. These terms are only used to distinguish two structural elements. Therefore, the first structural element in one embodiment can be referred to as the second structural element in other embodiments. Each embodiment described and illustrated herein includes its complementary embodiment. Furthermore, in this specification, "and / or" includes at least one of the structural elements listed before and after.

[0073] In the specification, as long as it is not clearly indicated in the context, the expression of the singular includes the expression of the plural. In addition, the terms such as "including" or "having" are used to specify the existence of the features, numbers, steps, structural elements or their combinations recorded in the specification, but do not exclude the existence or additional possibility of one or more other features, steps, structural elements or their combinations.

[0074] Furthermore, in the following description of the present invention, if it is determined that the specific description of a related well-known function or structure makes the gist of the present invention unclear, the detailed description thereof will be omitted.

[0075] Figure 1 FIG. 1 is a flow chart for illustrating a method for preparing a solid electrolyte according to a first embodiment of the present invention.

[0076] Reference Figure 1 , preparing a mixed solution including a thiophenium salt and a hydrogen fluoride precursor (step S110).

[0077] According to one embodiment, the thiophenium salt may be prepared by reacting an alkyl precursor solution with thiophene.

[0078] In this case, the alkyl precursor solution is prepared by adding an alkyl precursor substance to a solvent and stirring the solvent at room temperature. For example, the solvent may be acetonitrile. Specifically, for example, the alkyl precursor substance may be one of dichloromethane represented by the following chemical formula 1, ethyl chloride represented by the following chemical formula 2, propyl chloride represented by the following chemical formula 3, or butyl chloride represented by the following chemical formula 4.

[0079] <Chemical Formula 1>

[0080]

[0081] <Chemical Formula 2>

[0082]

[0083] <Chemical formula 3>

[0084]

[0085] <Chemical Formula 4>

[0086]

[0087] The thiophenium salt can be prepared by titrating the thiophene in the alkyl precursor solution prepared above and then reacting. Unlike the above, when a large amount of thiophene is added to the alkyl precursor solution at one time, the reactivity between the thiophene and the alkyl precursor substance decreases, and thus it is difficult to prepare the thiophenium salt.

[0088] Therefore, as described above, when the thiophene is titrated into the alkyl precursor solution, the reactivity between the thiophene and the alkyl precursor substance can be improved. In other words, the yield of the thiophenium salt can be improved.

[0089] In this case, the reaction time can be increased by reducing the chain length of the alkyl precursor. Therefore, the longer the chain length, the higher the reaction temperature can be, thereby increasing the reactivity of the alkyl precursor and the thiophene.

[0090] Thus, the thiophenium salt may include an alkyl group bonded to the sulfur element of the thiophenium. For example, the thiophenium salt may be a thiophenium chloride including one of a methyl group, an ethyl group, a propyl group, or a butyl group.

[0091] Specifically, for example, in the case where the alkyl precursor solution includes dichloromethane represented by the chemical formula 1, after the thiophene is titrated into the solution including the dichloromethane, a reaction is performed at room temperature to prepare the thiophenium salt in which the carbon atom of the dichloromethane is combined with the sulfur element of the thiophene. In other words, the thiophenium salt including a methyl group represented by the following chemical formula 5 can be prepared.

[0092] <Chemical Formula 5>

[0093]

[0094] As another example, in the case where the alkyl precursor solution includes ethyl chloride represented by the chemical formula 2, the thiophene is titrated into the solution including the ethyl chloride, and then reacted at a temperature higher than room temperature to prepare the thiophenium salt in which the ethyl chloride is combined with the sulfur element at the first position of the thiophene. In other words, the thiophenium salt including the ethyl group represented by the following chemical formula 6 can be prepared.

[0095] <Chemical Formula 6>

[0096]

[0097] As another example, when the alkyl precursor solution includes chloropropane represented by the chemical formula 3, the thiophene is titrated into the solution containing the chloropropane, and then the thiophene is reacted at a temperature higher than room temperature to prepare the thiophene salt in which the chloropropane is bonded to the sulfur element at the 1st position of the thiophene. In other words, the thiophene salt including a propyl group represented by the following chemical formula 7 can be prepared.

[0098] <Chemical Formula 7>

[0099]

[0100] As another example, when the alkyl precursor solution includes chlorobutane represented by the chemical formula 4, the thiophene is titrated into the solution including the chlorobutane, and then the thiophene is reacted at a temperature higher than room temperature to prepare the thiophene salt in which the chlorobutane is bonded to the sulfur element at the 1st position of the thiophene. In other words, the thiophene salt including a butyl group represented by the following chemical formula 8 can be prepared.

[0101] <Chemical Formula 8>

[0102]

[0103] The hydrogen fluoride precursor may be prepared by stirring a solution containing hydrofluoric acid and water. Specifically, for example, the hydrogen fluoride precursor may be prepared by adding the remaining amount of water to hydrofluoric acid having a concentration of 1 M and stirring the solution.

[0104] The mixed solution may be reacted to prepare a compound combining thiophenium and hydrogen fluoride (step S120 ).

[0105] Specifically, for example, the mixed solution is reacted at a temperature of -70°C or less for 24 hours to prepare the compound in which the thiophenium and the hydrogen fluoride represented by the following Chemical Formula 9 are bonded.

[0106] <Chemical Formula 9>

[0107]

[0108] Different from the above, when the mixed solution is reacted at room temperature, the hydrogen fluoride precursor can evaporate. Specifically, the hydrogen fluoride precursor has a boiling point below room temperature and can volatilize at room temperature.

[0109] Therefore, as described above, when the mixed solution is reacted at a temperature of -70° C., the compound can be easily prepared. Furthermore, as the reaction temperature is lowered, the loss of hydrogen fluoride is reduced, thereby reducing the reaction time.

[0110] As described above, the compound may include the alkyl group combined with the sulfur element of the thiophenium. In this case, the longer the chain of the alkyl group, the more the molecular weight of the thiophenium can be increased. As a result, the ion conductivity of the compound may be reduced. Specifically, for example, when the alkyl group is a methyl group, the compound may have a relatively high ion conductivity, and when the base group is a butyl group, the compound may have a relatively low ion conductivity.

[0111] As described above, the compound may be formed by combining a cation including the thiophenium and an anion including the hydrogen fluoride, and the compound may have a crystalline phase.

[0112] Specifically, the compound may have a first crystalline phase and a second crystalline phase according to temperature. For example, the first crystalline phase may be formed in a temperature range of 28° C. to 90° C., and the second crystalline phase may be formed in a temperature range of 22° C. to 28° C. In this case, the compound may induce a solid-liquid state change at a temperature of 90° C. or higher.

[0113] Figure 2 A diagram showing the crystal structure of a solid electrolyte according to an example of the present invention.

[0114] Reference Figure 2 , a solid electrolyte comprising the above compound and a lithium salt can be prepared. Figure 2 As shown, the unit cell of the compound may have an orthorhombic crystal structure, the thiophenium is provided to the vertices and the center of the face of the crystal structure, and the hydrogen fluoride is provided to the edge center of the crystal structure. In this case, the solid electrolyte may arbitrarily provide the lithium salt to the interstitial sites of the crystal structure. Specifically, the lithium salt may be lithium hydrogen fluoride. Therefore, the solid electrolyte may be prepared by the reaction of the compound and the lithium hydrogen fluoride.

[0115] In this case, the lithium hydrogen fluoride can be prepared by adding a lithium salt to the hydrogen fluoride precursor and reacting at a temperature lower than room temperature. Figure 1 As described above, the lithium hydrogen fluoride can be prepared using the hydrogen fluoride precursor. Thus, the reaction can be carried out at a temperature lower than room temperature to prevent the evaporation of the hydrogen fluoride precursor.

[0116] Specifically, for example, when the lithium salt is lithium chloride (LiCl), the lithium hydrogen fluoride can be prepared by adding lithium chloride to the hydrofluoric acid aqueous solution having a concentration of 1 M and reacting for 24 hours at a temperature below -70°C. In this case, the lithium hydrogen fluoride can be prepared by an anion exchange reaction.

[0117] The solid electrolyte can be prepared by heating the compound at a temperature higher than room temperature and adding the lithium fluoride prepared as above to the compound. For example, the solid electrolyte can be prepared by adding 1 mol % to 10 mol % of the lithium fluoride as compared to the compound. Figure 2 As shown, the lithium salt can be provided to the intrusive position of the crystal structure of the compound, thereby being able to easily move within the crystal structure. Therefore, the more the amount of lithium fluoride added increases, the higher the ion conductivity of the solid electrolyte can be.

[0118] Furthermore, for example, the solid electrolyte may have a crystalline phase in a temperature range of 28 to 70° C. by inducing a solid-liquid state change under the above temperature conditions. In other words, the solid electrolyte may have a melting point lower than the melting point (solid-liquid state change temperature) of the above compound by coating lithium, and may change the solid-solid state change temperature.

[0119] According to an embodiment of the present invention, the compound and the solid electrolyte may present a relatively similar pattern in an X-ray diffraction pattern (XRD). However, unlike the compound, the solid electrolyte may present a lithium-enriched phase. Thus, the compound and the solid electrolyte may have different crystal orientations.

[0120] The solid electrolyte containing the above-mentioned compound of the embodiment of the present invention or the above-mentioned solid electrolyte coated with lithium can be used as an electrolyte of a secondary battery. For example, the above-mentioned secondary battery may include a positive electrode, a negative electrode and the above-mentioned electrolyte. In this case, the above-mentioned electrolyte may be formed between the above-mentioned positive electrode and the above-mentioned negative electrode.

[0121] A method for designing a solid electrolyte according to an embodiment of the present invention is described.

[0122] The solid electrolyte may include a compound in which a cation and an anion are bonded. In this case, the cation and the anion may be selected so as to have the maximum ion conductivity within a range that satisfies the condition that the compound has a crystalline phase.

[0123] The condition that the above-mentioned compound has a crystalline phase can be that the molecular weight of the above-mentioned cation is 95g / mol or more. In this case, the above-mentioned cation may include a five-membered heterocyclic compound, and the above-mentioned heterocyclic compound may have an element in sulfur, nitrogen, oxygen or phosphorus. Specifically, for example, the above-mentioned cation may include a thiophenium (Thiophenium) represented by the following chemical formula 10, a thiazolium (Thiazolium) represented by the following chemical formula 11, a phosphine (Phospholanium) represented by the following chemical formula 12, an oxathiolanium (Oxathiolanium) represented by the following chemical formula 13 or chemical formula 14, or a thiazolidinium (Thiazolidinium) represented by the following chemical formula 15.

[0124] <Chemical formula 10>

[0125]

[0126] <Chemical Formula 11>

[0127]

[0128] <Chemical Formula 12>

[0129]

[0130] <Chemical Formula 13>

[0131]

[0132] <Chemical Formula 14>

[0133]

[0134] <Chemical Formula 15>

[0135]

[0136] The condition for the compound to have a crystalline phase may be that the molecular weight of the anion is greater than 60 g / mol, and the hydrogen ion concentration (pH) of the anion is less than 3. Specifically, for example, the anion may be one of hydrogen fluoride (Fluorohydrogenate) represented by the following chemical formula 16, cyano (nitroso) methanide (cyano (nitroso) methanide) represented by the following chemical formula 17, or tetrazoline (Tetrazoline) represented by the above chemical formula 18.

[0137] <Chemical Formula 16>

[0138]

[0139] <Chemical Formula 17>

[0140]

[0141] <Chemical Formula 18>

[0142]

[0143] Different from the above, when the above anion has a molecular weight of less than 60g / mol, the above compound can exist in a liquid state. In other words, when the above anion has a molecular weight of less than 60g / mol, it is difficult to form a solid having a crystalline phase. Specifically, for example, in the above compound, when the above cation is one of thiophenium represented by the above chemical formula 10 or thiazolium represented by the above chemical formula 11, and the above anion is one of oxohydrogenate represented by the following chemical formula 19 or cyanate represented by the following chemical formula 20, the above compound can exist in a particulate liquid state.

[0144] <Chemical formula 19>

[0145] O(HO)O x -

[0146] <Chemical formula 20>

[0147] O==C==N -

[0148] Therefore, as described above, in the case where the molecular weight of the above-mentioned anion is greater than 60g / mol, the above-mentioned compound can easily have a crystalline phase. Specifically, for example, in the above-mentioned compound, in the case where the above-mentioned cation is one of thiophenium represented by the above-mentioned chemical formula 10 or thiazolium represented by the above-mentioned chemical formula 11, and the above-mentioned anion is one of hydrogen fluoride represented by the above-mentioned chemical formula 16, cyano (nitroso) methane represented by the above-mentioned chemical formula 17, or tetrazoline represented by the above-mentioned chemical formula 18, the above-mentioned compound can exist in a solid state having the above-mentioned crystalline phase.

[0149] Thus, when the molecular weight of the cation is 95 g / mol or more, the molecular weight of the anion is greater than 60 g / mol, and the hydrogen ion concentration (pH) of the anion is less than 3, the compound may have a crystalline phase. In this case, the condition that the compound has the crystalline phase may be satisfied, and the fusion entropy of the compound is 15 to 25 J / Kmol. Thus, the crystalline phase may have flexibility.

[0150] Different from the above, when the melting entropy is less than 10 J / Kmol, the compound may have a liquid state. Therefore, it is difficult for the compound to have a crystalline phase. And, when the melting entropy is greater than 35 J / Kmol, the compound may have a crystalline solid state without flexibility.

[0151] Therefore, as described above, according to the embodiment of the present invention, the entropy of fusion may be 15 to 25 J / Kmol, and thus, the compound may easily have a crystalline phase and have high ion conductivity.

[0152] The solid electrolyte containing the above-mentioned compound of the embodiment of the present invention can be used as an electrolyte of a secondary battery. For example, the above-mentioned secondary battery may include a positive electrode, a negative electrode and an electrolyte. In this case, the above-mentioned electrolyte may be formed between the above-mentioned positive electrode and the above-mentioned negative electrode.

[0153] The compound of the first embodiment of the present invention may be an organic piezoelectric material having piezoelectric properties.

[0154] Specifically, in this case, the compound may be a polycrystal having a plurality of microcrystals. Also, as described above, the crystalline structure of the compound may be flexible. Therefore, the cation and / or the anion may be displaced in the crystalline structure. Thus, ionic polarization may occur through the relative displacement of the cation and the anion.

[0155] Unlike the above compounds, inorganic compounds composed of inorganic substances can be subjected to polarization treatment (poling) under high voltage conditions. As a result, the above inorganic compounds can have piezoelectric properties. In addition, the above inorganic compounds can be subjected to polarization treatment (poling) under high voltage conditions. Figure 1 The compound is prepared by heat treatment under the temperature conditions described above for the preparation of the compound.

[0156] However, as described above, the above compounds of the embodiments of the present invention can be polarized under relatively low voltage conditions to have piezoelectric properties. Figure 1As described above, the above compound can be prepared at room temperature or below room temperature. Therefore, compared with the above inorganic compound, the time and cost of the preparation process of the above compound can be reduced.

[0157] Specifically, the compound may have a piezoelectric coefficient of 105 pC / N to 125 pC / N in a temperature range of room temperature to 110°C. In this case, the compound may have a piezoelectric coefficient of 109 pC / N under room temperature conditions. In addition, the compound may change state into other crystalline structures (phase transition) under a temperature condition of 127°C, and thus, the compound may not exhibit piezoelectric properties. Therefore, the compound may have piezoelectric properties in a temperature range below 127°C.

[0158] Furthermore, the compound may have a piezoelectric coefficient of 105 pC / N to 125 pC / N in a frequency range of 25 Hz to 250 Hz. In this case, the compound may have a piezoelectric coefficient corresponding to each frequency value. That is, when vibration mechanical energy represented by the frequency is applied to the compound, the compound may be converted into different electrical signals according to the energy value applied. Thus, a piezoelectric device including the compound may be easily manufactured.

[0159] Figure 3 FIG. 4 is a schematic diagram of a self-generating secondary battery including an organic piezoelectric material according to an embodiment of the present invention.

[0160] Reference Figure 3 , the self-generating secondary battery may include a positive electrode 160, a negative electrode 120 and an electrolyte 140, wherein the electrolyte 140 is disposed between the positive electrode 160 and the negative electrode 120. In this case, the positive electrode 160 and the negative electrode 120 may include a positive electrode active material 150 and a negative electrode active material 130, respectively. Figure 3 As shown, the positive electrode active material 150 and the negative electrode active material 130 may be provided in the form of particles on the surface of the positive electrode 160 and the negative electrode 120 , respectively, or may be provided by being mixed in the positive electrode 160 and the negative electrode 120 , respectively.

[0161] The electrolyte 140 may include a piezoelectric body. Thus, a self-generating secondary battery that converts vibration mechanical energy generated by movement of a human body or wind, waves, etc. into electrical energy and stores the energy can be easily prepared.

[0162] In this case, the electrolyte 140 may be a solid electrolyte including the compound prepared according to an embodiment of the present invention and a lithium salt.

[0163] As described above, the compound may have a high piezoelectric constant. Also, the compound may have a high ionic conductivity. Specifically, for example, when the compound is a compound of the methylthiophenium and the hydrogen fluoride, the ionic conductivity of the compound may be 126 S / cm. Thus, the solid electrolyte may be easily prepared by mixing the compound with a lithium salt.

[0164] Furthermore, in the self-generating secondary battery, a first protective layer 170 may be formed outside the positive electrode 160, and a second protective layer 110 may be formed outside the negative electrode 120. Thus, the positive electrode 160, the negative electrode 120, and the electrolyte 140 may be protected from the external environment. In this case, the first protective layer 170 and the second protective layer 110 may be a polymer resin. Specifically, for example, the first protective layer 170 and the second protective layer 110 may include high temperature polyimide (Kapton), polyimide (PI), polyethylene terephthalate (PET), and the like.

[0165] On the other hand, as described above, the solid electrolyte may include the compound and a lithium salt. Figure 2 The unit cell of the compound may have an orthorhombic crystal structure, the thiophenium is provided to, and the hydrogen fluoride is provided to. In this case, Figure 2 As shown, the solid electrolyte can provide the lithium salt to any interstitial sites of the crystal structure. Therefore, the solid electrolyte can be prepared by reacting the compound with the lithium hydrogen fluoride.

[0166] When an external force is applied to the self-generating secondary battery of the embodiment of the present invention, a piezoelectric field may be generated in the electrolyte 140 containing the compound. Specifically, a piezoelectric field may be generated from the upper portion of the electrolyte 140 adjacent to the positive electrode 160 toward the lower portion of the electrolyte 140 adjacent to the negative electrode 120. By applying the piezoelectric field from the positive electrode 160 toward the negative electrode 120, lithium ions may move from the positive electrode active material 150 to the negative electrode active material 130. Thus, the charging operation of the self-generating secondary battery may be performed by an external force.

[0167] Figure 4 1 is a diagram showing a cross-sectional view of a piezoelectric sensor including an organic piezoelectric material according to an embodiment of the present invention and a driving principle. Specifically, Figure 4 Part (a) is a cross-sectional view of the piezoelectric sensor before an external force is applied. Figure 4Part (b) is a cross-sectional view of the piezoelectric sensor with an external force applied. The first electrode 210 , the second electrode 230 , and the piezoelectric material layer 220 are disposed between the first electrode 210 and the second electrode 230 .

[0168] In this case, the piezoelectric material layer 220 may be polycrystalline. Thus, the piezoelectric material layer 220 may be composed of a plurality of micro crystals 222. Figure 4 As shown in part (a) of FIG. 1 , before an external force is applied to the piezoelectric sensor, the plurality of minute crystals 222 may have different polarization directions.

[0169] On the contrary, Figure 4 As shown in part (b) of FIG. 1 , when an external force is applied to the piezoelectric sensor, the plan inside the plurality of microcrystals 222 may be formed along one direction. Thus, a piezoelectric field may be formed between the first electrode 210 and the second electrode 230, thereby forming a potential difference between the first electrode 210 and the second electrode 230.

[0170] Figure 5 FIG. 4 is a block diagram of a device including an organic piezoelectric substance according to an embodiment of the present invention.

[0171] Reference Figure 5 The above-mentioned device can be composed of a control unit 320 that converts the electrical signal received from the detection unit 310, the driving unit 330 and the above-mentioned detection unit 310 into physical energy to control the above-mentioned driving device 330.

[0172] The detection unit 310 may detect changes in the external environment, convert the changes into electrical signals, and provide the electrical signals to the control unit 320. In this case, the changes in the external environment may be selected in various ways according to the purpose of the device.

[0173] The control unit 320 may be an actuator including a piezoelectric material. Thus, the piezoelectric material may induce polarization through the electrical signal provided by the detection unit 310, and the electrical signal may be converted into physical energy. In this case, referring to Figure 1 to Figure 2 The compound may have piezoelectric properties through spontaneous ionic polarization. In addition, the compound may have a high piezoelectric coefficient and may be provided to the piezoelectric material of the actuator. For example, the actuator may be a motor, a switch, and the like.

[0174] The driving unit 330 may be a device that can be driven by the physical energy converted in the control unit 320. For example, the driving unit 330 may be a lighting device, a mechanical device, or the like.

[0175] Figure 6FIG. 1 is a flow chart for illustrating a method for preparing a solid electrolyte according to a second embodiment of the present invention.

[0176] Reference Figure 6 , a mixed solution including a thiazolium salt and a hydrogen fluoride precursor may be prepared (step S110 ).

[0177] According to one embodiment, the thiazolium salt may be prepared by reacting an alkyl precursor solution with thiazoline.

[0178] In this case, the alkyl precursor solution can be prepared by adding an alkyl precursor substance to a solvent and then stirring the solution under normal temperature. For example, the solvent can be acetonitrile. Specifically, for example, the alkyl precursor substance can be one of dichloromethane represented by the following chemical formula 21, ethyl chloride represented by the following chemical formula 22, propylchloride represented by the following <chemical formula 23>, or butyl chloride represented by the following chemical formula 24.

[0179] <Chemical Formula 21>

[0180]

[0181] <Chemical Formula 22>

[0182]

[0183] <Chemical Formula 23>

[0184]

[0185] <Chemical Formula 24>

[0186]

[0187] The thiazolium salt can be prepared by titrating the thiazoline into the alkyl precursor solution prepared as above and then reacting the thiazoline. Different from the above, when a large amount of the thiazoline is added to the alkyl precursor solution at one time, the Brahman image between the thiazoline and the alkyl precursor substance can be reduced, thus, it is difficult to prepare the thiazolium salt.

[0188] Therefore, as described above, when the thiazoline is titrated into the alkyl precursor solution, the reactivity between the thiazoline and the alkyl precursor substance can be improved. In other words, the yield of the thiazolium salt can be improved.

[0189] In this case, the longer the chain length of the alkyl precursor substance is, the longer the reaction time can be. Therefore, the longer the chain length is, the higher the reaction temperature can be, thereby improving the reactivity of the alkyl precursor substance and the thiazoline.

[0190] Thus, the thiazolium salt may include an alkyl group bonded to the nitrogen atom of the thiazolium. For example, the thiazolium salt may be a thiazolium chloride including one of a methyl group, an ethyl group, a propyl group, and a butyl group.

[0191] Specifically, for example, when the alkyl precursor solution includes dichloromethane represented by the chemical formula 1, the thiazoline is titrated into the solution including the dichloromethane, and then reacted at room temperature to prepare the thiazolium salt in which the carbon atom of the dichloromethane is combined with the nitrogen element of the thiazoline. In other words, the thiazolium salt including the methyl group represented by the following chemical formula 25 can be prepared.

[0192] <Chemical Formula 25>

[0193]

[0194] As another example, in the case where the alkyl precursor solution includes ethyl chloride represented by the chemical formula 2, the thiazoline is titrated into the solution including the ethyl chloride, and then reacted at a temperature higher than room temperature to prepare the thiazolium salt in which the ethyl chloride is combined with the nitrogen element at the 1st position of the thiazoline. In other words, the thiazolium salt including the ethyl group represented by the following chemical formula 26 can be prepared.

[0195] <Chemical Formula 26>

[0196]

[0197] As another example, in the case where the alkyl precursor solution includes chloropropane represented by the chemical formula 3, the thiazoline is titrated into the solution including the chloropropane, and then reacted at a temperature higher than room temperature to prepare the thiazolium salt in which the chloropropane is bonded to the nitrogen element at the 1st position of the thiazoline. In other words, the thiazolium salt including a propyl group represented by the following chemical formula 27 can be prepared.

[0198] <Chemical Formula 27>

[0199]

[0200] As another example, when the alkyl precursor solution contains chlorobutane represented by the chemical formula 4, the thiazoline is titrated into the solution containing the chlorobutane, and then the thiazoline is reacted at a temperature higher than room temperature to prepare the thiazolium salt in which the chlorobutane is bonded to the nitrogen element at the 1st position of the thiazoline. In other words, the thiazolium salt containing a butyl group represented by the following chemical formula 8 can be prepared.

[0201] <Chemical formula 28>

[0202]

[0203] The hydrogen fluoride precursor may be prepared by stirring a solution containing hydrofluoric acid and water. Specifically, for example, the hydrogen fluoride precursor may be prepared by adding the remaining amount of water to hydrofluoric acid having a concentration of 1 M and stirring the solution.

[0204] The mixed solution is reacted to prepare a compound combining thiazolium and hydrogen fluoride (step S120).

[0205] Specifically, for example, the mixed solution is reacted at a temperature of -70°C or less for 24 hours to prepare the compound in which the thiazolium and the hydrogen fluoride represented by the following Chemical Formula 29 are bonded.

[0206] <Chemical Formula 29>

[0207]

[0208] Different from the above, when the mixed solution is reacted at room temperature, the hydrogen fluoride precursor can evaporate. Specifically, the hydrogen fluoride precursor has a boiling point below room temperature, and thus can volatilize at room temperature.

[0209] Therefore, as described above, when the mixed solution is reacted at a temperature of -70° C., the compound can be easily prepared. In addition, the reaction temperature is lowered, the loss of hydrogen fluoride can be reduced, and thus the reaction time can be reduced.

[0210] As described above, the compound may be formed by combining a cation including the thiazolium and an anion including the hydrogen fluoride, and the compound may have a crystalline phase.

[0211] A solid electrolyte comprising the above-mentioned compound and a lithium salt may be prepared. In this case, the above-mentioned lithium salt may be provided arbitrarily to the interstitial sites of the above-mentioned crystalline structure of the above-mentioned compound. Specifically, the above-mentioned lithium salt may be lithium hydrogen fluoride. Therefore, the above-mentioned solid electrolyte may be prepared by reacting the above-mentioned compound and the above-mentioned lithium hydrogen fluoride.

[0212] In this case, the lithium hydrogen fluoride can be prepared by adding a lithium salt to the hydrogen fluoride precursor and reacting at a temperature lower than room temperature. Figure 1 As described above, the lithium hydrogen fluoride can be prepared using the hydrogen fluoride precursor. Thus, the reaction can be carried out at a temperature lower than room temperature to prevent the hydrogen fluoride precursor from evaporating.

[0213] Specifically, for example, in the case of the lithium salt lithium chloride (LiCl), the lithium hydrogen fluoride can be prepared by adding lithium chloride to the hydrofluoric acid aqueous solution having a concentration of 1 M and reacting for 24 hours at a temperature below -70°C. In this case, the lithium hydrogen fluoride can be prepared by an anion exchange reaction.

[0214] The above-mentioned solid electrolyte can be prepared by heating the above-mentioned compound under a temperature condition higher than room temperature, and at the same time, adding the above-mentioned lithium fluoride prepared as above to the above-mentioned compound. For example, the above-mentioned solid electrolyte can be prepared by adding 1 mol% to 10 mol% relative to the above-mentioned compound. The above-mentioned lithium salt can be provided to the above-mentioned intrusive position of the crystal structure of the above-mentioned compound, thereby being able to easily move within the above-mentioned crystal structure. Therefore, the above-mentioned solid electrolyte can improve the ion conductivity by adding the above-mentioned lithium fluoride.

[0215] The solid electrolyte containing the compound of the embodiment of the present invention or the solid electrolyte coated with lithium can be used as an electrolyte of a secondary battery. For example, the secondary battery may include a positive electrode, a negative electrode and the electrolyte. In this case, the electrolyte may be formed between the positive electrode and the negative electrode.

[0216] The following describes a specific method for preparing the solid electrolyte according to the first embodiment of the present invention and the results of evaluating its characteristics.

[0217] Preparation of the compound of Experimental Example 1-1

[0218] The alkyl precursor material is prepared by dichloromethane represented by the above Chemical Formula 1.

[0219] Acetonitrile was provided in a conical flask, and the dichloromethane was added thereto, followed by stirring at room temperature for 10 minutes to prepare an alkyl precursor solution. In this case, the preparation of the alkyl precursor solution was performed in a glove box without moisture.

[0220] After thiophene was titrated into the alkyl precursor solution and stirred, the uniformly mixed solution was slowly stirred at room temperature to prepare a thiophenium salt having a methyl group.

[0221] The washing step is performed by supplying the thiophenium salt and a solvent of ethyl acetate and diethyl ether to a rotary concentrator.

[0222] 1 M hydrofluoric acid and the balance of water were added to a conical flask, followed by stirring for 10 minutes to prepare a hydrogen fluoride precursor.

[0223] The thiophenium salt was added to the hydrogen fluoride precursor to prepare a mixed solution, and the mixed solution was left at -70°C for 24 hours to prepare a compound mixed with the thiophenium salt and the hydrogen fluoride.

[0224] After the compound was placed in a glove box with a nitrogen environment, it was left at room temperature for 2 to 3 hours to remove volatile gas. Thereafter, the compound was placed in the rotary concentrator and subjected to a drying process to prepare the compound of Experimental Example 1-1.

[0225] Preparation of the compound of Experimental Example 1-2

[0226] The same method as in Experimental Example 1-1 was used to prepare ethyl chloride represented by Chemical Formula 2 as the alkyl precursor instead of dichloromethane. In addition, in the preparation step of thiophenium, the reaction was performed at 60 to 80° C. for 2 to 3 days instead of at room temperature for 4 days to prepare the compound of Experimental Example 1-2.

[0227] Preparation of the compounds of Experimental Examples 1-3 thing

[0228] The same method as in Experimental Example 1-1 was used to prepare the alkyl precursor, except that propyl chloride represented by the chemical formula 3 was used instead of dichloromethane. In addition, in the preparation step of the thiophenium, the reaction was performed at 60 to 80° C. for 2 to 3 days instead of at room temperature for 4 days to prepare the compound of Experimental Example 1-3.

[0229] Preparation of compounds of Experimental Examples 1-4

[0230] The same method as in Experimental Example 1-1 was used to prepare butyl chloride represented by the chemical formula 4 as the alkyl precursor instead of dichloromethane. In addition, in the step of preparing the thiophenium, the compound of Experimental Example 1-4 was prepared by reacting at a temperature of 60 to 80° C. for 2 to 3 days instead of reacting at room temperature for 4 days.

[0231] Preparation of the solid electrolyte of Experimental Example 2-1

[0232] After adding a 1 M hydrofluoric acid aqueous solution and lithium chloride (LiCl) into a container, the container was left to stand at a temperature of -70°C for 24 hours to prepare lithium hydrogen fluoride.

[0233] The methyl group of Experimental Example 1-1 was heated to a compound, and at the same time, 1 mol % of the lithium hydrogen fluoride was added and incubated for 2 hours to prepare a solid electrolyte of Experimental Example 2-1.

[0234] Preparation of the solid electrolyte of Experimental Example 2-2

[0235] The solid electrolyte of Experimental Example 2-2 was prepared by the same method as that of Experimental Example 2-1, except that 5 mol % of the lithium hydrogen fluoride was added instead of 1 mol %.

[0236] Preparation of the solid electrolyte of Experimental Example 2-3

[0237] The solid electrolyte of Experimental Example 2-3 was prepared by the same method as that of Experimental Example 2-1, except that 10 mol % of the lithium hydrogen fluoride was added instead of 1 mol %.

[0238] Preparation of the compound of Comparative Example 1-1

[0239] The cation is prepared as thiazolium represented by the above Chemical Formula 11. In this case, the above R1 represents an ethyl group.

[0240] As the anion, the compound of Comparative Example 1-1 was prepared using hydrogen fluoride prepared according to the above Experimental Example 1-1.

[0241] Preparation of the compound of Comparative Example 1-2

[0242] The cation is prepared as a phosphonium represented by the above Chemical Formula 12.

[0243] In this case, the above R1 and R2 are ethyl and butyl respectively.

[0244] As the anion, the compound of Comparative Example 1-2 was prepared using hydrogen fluoride prepared according to the above Experimental Example 1-1.

[0245] Preparation of the compounds of Comparative Examples 1-3

[0246] The cation prepared is pyrrolidinium represented by the following chemical formula 30.

[0247] <Chemical formula 30>

[0248]

[0249] In this case, the above R1 and R2 are ethyl and butyl, respectively.

[0250] As the anion, the compound of Comparative Example 1-3 was prepared using hydrogen fluoride prepared according to the above Experimental Example 1-1.

[0251] Preparation of the compounds of Comparative Examples 1-4

[0252] The cation is prepared as an imidazolium represented by the above Chemical Formula 31. In this case, the above R1 and R2 are methyl and ethyl, respectively.

[0253] <Chemical formula 31>

[0254]

[0255] As anion, the compound of Comparative Example 1-4 was prepared using hydrogen fluoride prepared according to the above Experimental Example 1-1.

[0256] Preparation of the compounds of Comparative Examples 1-5

[0257] In the cation, the nitrogen of the thiazolidinium represented by the above Chemical Formula 15 is bonded to a methyl group and an ethyl group, and the sulfur of the thiazolidinium is bonded to two methyl groups.

[0258] As the anion, the compound of Comparative Example 1-5 was prepared using hydrogen fluoride prepared according to the above Experimental Example 1-1.

[0259] Figure 7 It is a graph showing differential scanning calorimetry (DSC) of the compound of Experimental Example 1-1 of the present invention and the solid electrolyte of Experimental Example 2-3.

[0260] Reference Figure 7 In the compound of Experimental Example 1-1 and the solid electrolyte of Experimental Example 2-3, a state change between solid-liquid or solid-solid depending on temperature can be observed.

[0261] like Figure 7 As shown, the above compound observed a solid-liquid state change under a temperature condition of 90° C. In this case, the melting entropy of the above compound was 32 J / Kmol. On the contrary, the above solid electrolyte observed a solid-liquid state change under a temperature condition of 70° C., in this case, the melting entropy of the above solid electrolyte was 24 J / Kmol.

[0262] Furthermore, the above compound was observed to undergo a solid-solid state change twice. Thus, the above compound had a first crystalline phase in a temperature range of 28°C to 90°C and a second crystalline phase in a temperature range of 22°C to 28°C. In contrast, the above solid electrolyte was observed to undergo a solid-solid state change once, thus having a primary crystalline phase in a temperature range of 22°C to 70°C.

[0263] Therefore, the compound may further include the lithium salt, and the melting point* (solid-liquid state change temperature) may be reduced. Thus, the reduction of the melting entropy required for the state change may be confirmed. Furthermore, the compound may further include the lithium salt, and the change of the temperature at which the solid-solid state change occurs may be confirmed.

[0264] Figure 8 It is a graph showing the X-ray diffraction patterns (XRD) of the compound of Experimental Example 1-1 and the solid electrolyte of Experimental Example 2-2 of the present invention.

[0265] Reference Figure 8 , compared with the compound of Experimental Example 1-1, a change in the crystal structure was observed in the solid electrolyte of Experimental Example 2-2.

[0266] like Figure 8 As shown, the positions of the main peaks of the compound and the solid electrolyte are the same. On the contrary, it is observed that the intensities of the peaks are different. Therefore, the solid electrolyte also contains a lithium-rich phase, and it can be confirmed that the crystal orientation in the solid electrolyte changes compared with the compound.

[0267] As described above, the solid electrolyte may also contain a combination of different phases compared to the compound. In this case, the combination of different phases liquefies under relatively low temperature conditions, such as Figure 2 As shown, the solid electrolyte may have a lower melting point than the above compounds.

[0268] Fig. 9 This is a graph showing the ion conductivity of the compounds of Experimental Examples 1-1 to 1-4 of the present invention and the compounds of Comparative Examples 1-1 to 1-5 depending on the temperature.

[0269] Reference Fig. 9 The compounds of Experimental Examples 1-1 to 1-4 and the compounds of Comparative Examples 1-1 to 1-4 may contain the same anion, which may be hydrogen fluoride. Thus, the ion conductivity based on the change of the cation may be compared.

[0270] like Fig. 9As shown, the compounds of the experimental examples of the present invention exhibit higher ion conductivity than the compounds of the comparative examples. Moreover, the shorter the length of the alkyl chain, the higher the ion conductivity of the compounds of the experimental examples of the present invention. Specifically, the above compounds exhibit 46S / cm 2 Up to 126mS / cm 2 The ionic conductivity of the above compound with methyl group is 126mS / cm 2 The highest ionic conductivity.

[0271] [Table 1]

[0272] alkyl <![CDATA[Ionic conductivity (mS / cm 2 )]]> Experimental Example 1-1 methyl 126 Experimental Example 1-2 Ethyl 103 Experimental Examples 1-3 Propyl 68 Experimental Examples 1-4 Butyl 46

[0273] In addition to the compounds of Comparative Examples 1-1 to 1-5, the structures and ion conductivities of other compounds having high ion conductivity at room temperature are plotted in Table 2 below.

[0274] [Table 2]

[0275]

[0276] As shown in Table 2, the compound of Table 2 may contain one of thiazolium represented by the above Chemical Formula 11, phosphonium represented by the above Chemical Formula 12, thiazolidinium represented by the above Chemical Formula 15 (in a state where sulfur is fixedly bonded to two methyl groups, the alkyl group bonded to nitrogen is changed), imidazolium represented by the above Chemical Formula 31, or pyrrolidinium represented by the above Chemical Formula 30 as the above cation. Fig. 9 As shown in Table 1, it can be confirmed that the compounds of the experimental examples of the present invention have higher ion conductivity than the compounds of Table 2.

[0277] Fig.10 This is a graph showing the ion conductivity of the compound of Experimental Example 1-1 of the present invention and the solid electrolytes of Experimental Examples 2-1 to 2-3 depending on the temperature.

[0278] Reference Fig.10 , confirmed the reference Figure 5 The ion conductivity of the lithium salt added to the compound of Experimental Example 1-1 having the highest ion conductivity and the above compound. The solid electrolyte further comprises 1 mol % to 10 mol % of the lithium hydrogen fluoride relative to the above compound. Figure 2 As shown, the solid electrolyte can provide the lithium salt to any intrusive position of the crystal structure of the compound. Therefore, the lithium salt can easily move within the crystal structure, and thus, the solid electrolyte has a higher ion conductivity as the amount of lithium fluoride added increases.

[0279] In this case, the lithium salt can exhibit ion conductivity by moving to the intrusion type position where the lithium salt is not provided. Therefore, the more the intrusion type position where the lithium salt is provided increases, the more difficult it is for the lithium salt to move. Thus, when the amount of lithium hydrogen fluoride added is 5 mol percent or more, the ion conductivity becomes substantially constant (saturation).

[0280] Fig.11 This is a photograph of an electrolyte membrane coated with a solid electrolyte according to an example of the present invention.

[0281] Reference Fig.11 , a solid electrolyte membrane in the form of a film in which a solid electrolyte according to an embodiment of the present invention is coated on a polytetrafluoroethylene (PTFE) resin is photographed. In this case, the solid electrolyte membrane maintains the flexibility and transparency of the resin.

[0282] Figure 12 to Figure 13 : is a graph showing the cycle test results of the secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention.

[0283] Reference Figure 12 to Figure 13 , confirmed according to the reference Fig.11 The above contents include the charge and discharge characteristics of the secondary battery of the solid electrolyte in which the ion conductivity becomes substantially constant. In other words, the secondary battery includes the solid electrolyte of Experimental Example 2-2 of the present invention. In addition, the secondary battery includes LiFePO4 as a positive electrode, lithium metal as a negative electrode, and polyethylene (PE) as a separator between the positive electrode and the negative electrode.

[0284] In this case, the secondary battery performs a cycle test at a rate of 1C. In the first cycle, the secondary battery exhibits a Coulombic efficiency of 99.5% and a capacity of 158.6 mAh / g. In the 250th cycle, the secondary battery exhibits a Coulombic efficiency of 98% and a capacity of 155.5 mAh / g. Therefore, in 250 cycles, a Coulombic efficiency close to 99% can also be exhibited, and the secondary battery with excellent cycle stability is provided.

[0285] Fig.14 It is a graph showing the capacity maintenance rate at the charging and discharging speeds of the secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention.

[0286] Reference Fig.14 , confirmed for reference Figure 12 to Figure 13The prepared secondary battery changes the speed in a prescribed cycle to maintain the capacity of the secondary battery. In this case, the charging and discharging speed of the secondary battery is increased to 0.1C to 5C and then reduced to 1C again. Thus, when the charging and discharging speeds are 0.1C, 0.5C, 1C, 2C, 3C and 5C, the measured discharge capacities are 161.0mAh / g, 160.5mAh / g, 158.6mAh / g, 156.4, 153.8mAh / g and 148.9mAh / g, respectively. Therefore, it is confirmed that the secondary battery maintains a constant capacity regardless of the change in speed.

[0287] Fig.15 Graph showing resistance in a cycle test of a secondary battery including the solid electrolyte of Experimental Example 2-2 of the present invention.

[0288] Reference Fig.15 , measured in reference Figure 12 to Figure 13 In the prepared secondary battery, the interface resistance (interphase impedance, RSEI) and the electron transfer resistance (electron transfer resistance, RCT) in the first cycle and the 250th cycle. The above-mentioned interface resistance and the above-mentioned electron transfer resistance in the above-mentioned first cycle are 1.65Ω and 11.22Ω, respectively. The above-mentioned interface resistance and the above-mentioned electron transfer resistance in the above-mentioned 250th cycle are 1.75Ω and 11.65Ω, respectively. The more the number of cycles increases, the movement and diffusion of the elements contained in the structural elements of the above-mentioned secondary battery can occur. As a result, the resistance in the above-mentioned secondary battery can be increased, and the charging and discharging characteristics of the above-mentioned secondary battery are reduced. However, in the above-mentioned secondary battery comprising the solid electrolyte of the embodiment of the present invention, the increase in the above-mentioned resistance observed in the 250th cycle is relatively low. Therefore, it can be confirmed that the above-mentioned secondary battery comprising the solid electrolyte of the embodiment of the present invention has excellent chemical stability.

[0289] Fig.16 FIG. 4 is a graph showing the piezoelectric coefficient of the organic piezoelectric material according to the embodiment of the present invention.

[0290] Reference Fig.16 It can be confirmed that the organic piezoelectric material of the experimental example of the present invention exhibits piezoelectric properties in the range before the phase transition temperature. In this case, among the piezoelectric materials mainly used in the past, inorganic materials include barium titanate (BaTiO3), quartz, etc., and organic materials include polyvinylidene fluoride (PVDF), etc. The piezoelectric coefficients of the existing piezoelectric materials are formulated in the following Table 3.

[0291] [Table 3]

[0292] Piezoelectric material Types of piezoelectric materials Piezoelectric coefficient (pC / N) <![CDATA[001 direction, BaTiO3]]> Inorganic 90 Polyvinylidene fluoride Organic matter 23 quartz Inorganic 5

[0293] As shown in Table 3 and Fig.16 As shown, the organic piezoelectric material can have a piezoelectric coefficient of 109 pC / N at room temperature. Therefore, compared with the existing piezoelectric material, the organic piezoelectric material can have a higher piezoelectric coefficient.

[0294] like Fig.16 As shown, it was confirmed that the organic piezoelectric material had a piezoelectric coefficient of 105 pC / N to 125 pC / N in the temperature range from room temperature to 110° C. In addition, the organic piezoelectric material changed its state into another crystal structure under the temperature condition of 127° C., thereby confirming that the organic piezoelectric material did not have piezoelectric properties.

[0295] Fig.17 FIG. 4 is a graph showing the piezoelectric coefficient of the organic piezoelectric material according to the embodiment of the present invention.

[0296] Reference Fig.17 , it was confirmed that the organic piezoelectric material had a piezoelectric coefficient of 105 pC / N to 125 pC / N in the frequency range of 25 Hz to 250 Hz. And, the piezoelectric coefficient of the organic piezoelectric material was confirmed by increasing or decreasing the value of the frequency. In this case, it was confirmed that the compound had a corresponding piezoelectric coefficient for each frequency value.

[0297] Fig.18 FIG. 5 is a scanning electron microscope (SEM) photograph of the organic piezoelectric material according to an embodiment of the present invention.

[0298] Reference Fig.18 , a surface image of the organic piezoelectric material of the experimental example of the present invention was taken by a scanning electron microscope. Thus, the organic piezoelectric material has a solid state under normal temperature conditions.

[0299] Fig.19 FIG. 5 is a piezoelectric microscope (PFM) image of the organic piezoelectric material according to an embodiment of the present invention.

[0300] Reference Fig.19 The piezoelectric microscope applies an electromagnetic field to the sample at the tip of the piezoelectric microscope, thereby causing a physical change of expansion or compression in the sample. According to the physical change, the position of the tip of the piezoelectric microscope changes, thereby generating a piezoelectric microscope image.

[0301] like Fig.19 As shown, the surface image of the organic piezoelectric material of Experimental Example 1-1 of the present invention was confirmed by a piezoelectric microscope.

[0302] The following describes a specific method for preparing the solid electrolyte according to the second embodiment of the present invention and the results of evaluating its characteristics.

[0303] Preparation of the compound of Experimental Example 3-1 thing

[0304] As the alkyl precursor material, dichloromethane represented by the above Chemical Formula 21 was prepared.

[0305] Acetonitrile was provided in a conical flask, and the dichloromethane was added thereto, followed by stirring at room temperature for 10 minutes to prepare an alkyl precursor solution. In this case, the preparation of the alkyl precursor solution was performed in a glove box without moisture.

[0306] After thiazoline was added to the alkyl precursor solution and stirred, the uniformly mixed solution was slowly stirred at room temperature for 4 days to prepare a thiazolium salt having a methyl group.

[0307] The washing step is performed by supplying the thiazolium salt and a solvent of acetate and diethyl ether into a rotary concentrator.

[0308] 1 M hydrofluoric acid and the remainder of water were added to a conical flask, followed by stirring for 10 minutes to prepare a hydrogen fluoride precursor.

[0309] The thiazolium salt is added to the hydrogen fluoride precursor to prepare a mixed solution. The mixed solution is placed at a temperature of -70°C for 24 hours to prepare a compound in which the thiazolium salt and the hydrogen fluoride are combined.

[0310] After the compound was placed in a glove box with a nitrogen atmosphere, it was left at room temperature for 2 to 3 hours to remove volatile gas, and then placed in the rotary concentrator to perform a drying process, thereby preparing the compound of Experimental Example 3-1.

[0311] Preparation of the compound of Experimental Example 3-2

[0312] The same method as in Experimental Example 3-1 was used to prepare the alkyl precursor, except that ethyl chloride represented by Chemical Formula 22 was used instead of dichloromethane. In the preparation step of the thiazolium salt, the reaction was performed at 60° C. to 80° C. for 2 logs and 3 days instead of leaving the reaction at room temperature for 4 days to prepare the compound of Experimental Example 3-2.

[0313] Preparation of the compound of Experimental Example 3-3

[0314] The same method as in Experiment 3-1 was used to prepare the compound of Experiment 3-3, except that propyl chloride represented by the above-mentioned <Chemical Formula 23> was prepared as the above-mentioned alkyl precursor instead of the above-mentioned dichloromethane. In addition, in the preparation step of the above-mentioned thiazolium salt, the compound of Experiment 3-3 was prepared by reacting for 2 logs and 3 days at a temperature of 60° C. to 80° C. instead of leaving the reaction at room temperature for 4 days.

[0315] Preparation of Compounds of Experimental Example 3-4

[0316] The same method as in Experimental Example 3-1 was used to prepare the compound of Experimental Example 3-4 by replacing the dichloromethane with butyl chloride represented by Chemical Formula 24 as the alkyl precursor. In addition, in the preparation step of the thiazolium salt, the compound was prepared by reacting at a temperature of 60° C. to 80° C. for 2 logs and 3 days instead of reacting at room temperature for 4 days.

[0317] Preparation of the compound of Comparative Example 2-1

[0318] The cation is prepared as phosphonium represented by the above chemical formula 12. In this case, the above R1 and R2 represent alkyl groups shown in Table 4 below.

[0319] As the anion, the compound of Comparative Example 2-1 was prepared using hydrogen fluoride prepared according to the above Experimental Example 3-1.

[0320] Preparation of the compound of Comparative Example 2-2

[0321] The cation is imidazolium represented by the above Chemical Formula 31.

[0322] In this case, the above R1 and R2 each represent an alkyl group shown in Table 4 below.

[0323] As the anion, the compound of Comparative Example 2-2 was prepared using hydrogen fluoride prepared according to the above Experimental Example 3-1.

[0324] Preparation of Comparative Example 2-3 Compounds

[0325] The cation prepared is pyrrolidinium represented by the above chemical formula 30.

[0326] In this case, the above R1 and R2 each represent an alkyl group shown in Table 4 below.

[0327] The compound of Comparative Example 2-3 was prepared using hydrogen fluoride prepared according to the above Experimental Example 3-1 as an anion.

[0328] Preparation of the compound of Comparative Example 2-4

[0329] The cation is prepared as thiazolidinium represented by the above chemical formula 15. In this case, as shown in the following Table 4, the above R1 and R2 are alkyl groups bonded to nitrogen, and two methyl groups are fixedly bonded to sulfur.

[0330] As the anion, the compound of Comparative Example 2-4 was prepared using hydrogen fluoride prepared according to the above Experimental Example 3-1.

[0331] Fig. 20 This is a graph showing the ion conductivity of the compounds of Experimental Examples 3-1 and 3-4 of the present invention.

[0332] Reference Fig. 20 , the ionic conductivity of the compounds of Experimental Examples 3-1 and 3-4 was measured. The measurement results are as follows: Fig. 20 As shown, under normal temperature conditions, according to Experimental Example 3-1, in the case of having a methyl group, it was measured to be 45 mS / cm 2 According to Experimental Example 3-2, in the case of ethyl group, it was measured to be 74mS / cm 2 According to Experimental Example 3-3, in the case of a propyl group, the measured value is 18.9 mS / cm 2 According to Experimental Example 3-4, in the case of a butyl group, the measured value is 6.8 mS / cm 2 .

[0333] The compounds of Experimental Examples 3-1 to 3-4 of the present invention have high ion conductivity. In particular, according to Experimental Example 3-2, the compounds having an ethyl group have the highest ion conductivity.

[0334] As shown in Table 4 below, the ion conductivity of the compounds of Comparative Examples 2-1 to 2-4 in the gastrointestinal state was measured.

[0335] As shown in Table 4 below, compared with the compounds of Comparative Examples 2-1 to 2-4, it was confirmed that Experimental Example 3-2 of the present invention had significantly high ion conductivity in the case of the compound having an ethyl group, thiazolium and hydrogen fluoride bonded thereto.

[0336] [Table 4]

[0337]

[0338] Fig.21 This is a graph showing differential scanning calorimetry (DSC) of the compound of Experimental Example 3-1 of the present invention.

[0339] Reference Fig.21, a temperature-dependent state change was observed in the compound of Experimental Example 3-1. Specifically, Figure 3 As shown, it can be confirmed that there is a first crystal phase between -14°C and 110°C, and there is a second crystal phase between -80°C and -14°C.

[0340] Fig. 22 This is a graph showing the electrochemical window of the compound of Experimental Example 3-1 of the present invention.

[0341] Reference Fig. 22 In the case of the compound of Experimental Example 3-1, it was confirmed that there was an electrochemical window in the range of about 6V, which was about -3V to +3V.

[0342] That is, according to the examples of the present invention, it was confirmed that the compound in which a cation including thiazolium and an anion including hydrogen fluoride are combined maintains a solid state over a wide temperature range and has electrochemical stability and high ion conductivity.

[0343] The present invention is described in detail above through preferred embodiments, however, the scope of the present invention is not limited to the specific embodiments, but needs to be interpreted through the scope of the additional claims. Moreover, as long as one is of ordinary skill in the art to which the present invention belongs, various modifications and variations can be made without exceeding the scope of the present invention.

[0344] Industrial Applicability

[0345] The solid electrolyte and the secondary battery containing the same according to the embodiment of the present invention can be used in various industrial fields such as portable electronic devices, electric vehicles and ESS.

Claims

1. A solid electrolyte, characterized in that: A compound comprising a combination of a cation and an anion, wherein the cation is thiophenium, the anion is one of hydrogen fluoride, cyanomethane (nitroso) or tetrazoline, and the solid electrolyte further comprises a lithium salt. The unit cell of the above compound has an orthorhombic crystal structure. Providing the cations to the vertices and the center of the faces of the crystalline structure, providing the anions to the middle of the edges of the crystalline structure, and providing the lithium salt to any interstitial position of the crystalline structure; The above compound contains an alkyl group bonded to the sulfur element of the above thiophenium, and The alkyl group includes one of a methyl group, an ethyl group, a propyl group and a butyl group.

2. The solid electrolyte according to claim 1, characterized in that The longer the chain of the alkyl group is, the lower the ion conductivity of the compound is.

3. The solid electrolyte according to claim 1, characterized in that The higher the concentration of the lithium salt, the higher the ion conductivity.

4. The solid electrolyte according to claim 1, characterized in that The methyl group bonded to the sulfur element of the thiophenium has a crystalline phase in a temperature range of 28° C. to 70° C. in a heat flow spectrum based on temperature of differential scanning calorimetry.

5. The solid electrolyte according to claim 1, characterized in that When an external force is applied, the cations and the anions are displaced, so that the compound has piezoelectric properties.

6. A solid electrolyte, characterized in that A compound comprising a cation and an anion, wherein the cation is thiazolium, the anion is one of hydrogen fluoride, cyanomethane (nitroso) or tetrazoline, and The solid electrolyte further comprises a lithium salt, The unit cell of the above compound has an orthorhombic crystal structure. Providing the cations to the vertices and the center of the faces of the crystalline structure, providing the anions to the middle of the edges of the crystalline structure, and providing the lithium salt to any interstitial position of the crystalline structure; The above compound contains an alkyl group bonded to the nitrogen element of the above thiazolium, and The alkyl group includes a methyl group, an ethyl group or a propyl group.

7. The solid electrolyte according to claim 6, characterized in that The above compound contains an ethyl group bonded to the nitrogen element of the above thiazolium.

8. A self-generating secondary battery, characterized in that: It includes a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is located between the positive electrode and the negative electrode. The above electrolyte comprises the compound defined in any one of claims 1 to 5 or the compound defined in claim 6 or 7 and a lithium salt.

9. A method for preparing a solid electrolyte, characterized in that: include: A step of preparing a mixed solution of a thiophenium salt and a hydrogen fluoride precursor or a thiazolium salt and a hydrogen fluoride precursor; as well as a step of reacting the mixed solution at a temperature lower than room temperature to prepare a compound of thiophenium and hydrogen fluoride or a compound of thiazolium and hydrogen fluoride, Wherein, the solid electrolyte is the solid electrolyte according to any one of claims 1 to 5 or the solid electrolyte according to claim 6 or 7.

10. The method for preparing a solid electrolyte according to claim 9, characterized in that: The step of preparing the mixed solution includes the step of preparing the thiophenium salt or the thiazolium salt. The steps of preparing the above-mentioned thiophenium salt or the above-mentioned thiazolium salt include: a step of preparing an alkyl precursor solution; A step of preparing a cation source solution by titrating thiophene or thiazoline into the alkyl precursor solution; and a step of reacting the cation source solution to prepare a thiophenium salt or thiazolium salt containing the alkyl group; The alkyl group includes one of a methyl group, an ethyl group, a propyl group and a butyl group.

11. The method for preparing a solid electrolyte according to claim 9, characterized in that: The step of preparing the mixed solution comprises the step of preparing the hydrogen fluoride precursor. The step of preparing the hydrogen fluoride precursor includes the step of preparing the hydrogen fluoride precursor by stirring a solution containing hydrofluoric acid and water.

12. A method for preparing a solid electrolyte, characterized in that: Also includes: Steps for preparing lithium hydrofluoride; as well as A step of mixing the compound prepared in the method of claim 9 and the above-mentioned lithium hydrogen fluoride and subjecting the mixture to heat treatment to prepare a lithium-coated solid electrolyte, The steps of preparing the above lithium hydrogen fluoride include: The step of adding a lithium salt to an aqueous hydrofluoric acid solution to prepare a source solution; as well as The step of making the source solution react at a temperature lower than room temperature to prepare the lithium hydrogen fluoride.

Citation Information

Patent Citations

  • Composition for ionic liquid polymer electrolyte, ionic liquid polymer electrolyte prepared therefrom, and lithium secondary cell comprising the same

    KR1020140046611A

  • Ionic liquid and plastic crystal

    CN106715389A